2008
DOI: 10.5585/conssaude.v7i2.1063
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura trófica da avifauna em fragmentos florestais na Amazônia Oriental

Abstract: Neste estudo realizado em dois fragmentos florestais localizados no município de Paragominas, no Estado do Pará, Amazônia Oriental (entre as coordenadas geográficas 3o24’ e 3o38’ de latitude sul e 47o12’ e 47o40’ de longitude oeste), em outubro de 2007 e março de 2008, o objetivo é analisar os grupos de aves afetados pela fragmentação florestal e o isolamento dessas áreas, tendo como indicador ecológico a avifauna. O método utilizado para o registro da avifauna foi o de observações em pontos fixos. Para as áre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
2
1
5
Order By: Relevance
“…However, when compared to the data of [23] in Paragominas forest fragments in western Pará, where they found 123 species with only 48 sample hours, our wealth value is lower. Probably because our forest fragments represent a continuum that connects the left bank of the Xingu…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…However, when compared to the data of [23] in Paragominas forest fragments in western Pará, where they found 123 species with only 48 sample hours, our wealth value is lower. Probably because our forest fragments represent a continuum that connects the left bank of the Xingu…”
Section: Discussioncontrasting
confidence: 74%
“…Butas indicate the work of [23], the fragments in Paragominas can represent true islands with fauna densification, as already indicated in works with isolated fragments [24]. On the other hand, studies carried out in the Xingu basin indicate relatively high values of species diversity 197 species for Serra do Pardo [7] and 242 for the ecological station Terra do Meio [6], however the methodologies do not are comparable.…”
Section: Avifauna Of Two Forest Fragments Near the City Of Altamira mentioning
confidence: 98%
“…These results corroborate previous studies (Piratelli & Pereira, 2002;Donatelli et al, 2004;Roda, 2004;Roda & Pereira, 2005), who claim that this distribution is characteristic of well-preserved tropical forests. Other authors, however, have shown a predominance of insectivores and omnivores in tropical bird communities (Telino-Jr et al, 2005;Rodrigues et al, 2007;Dario, 2008 The importance of isolated patches for maintaining local bird biodiversity...…”
Section: Discussionmentioning
confidence: 99%
“…A composição da avifauna sofre variações conforme ocorrem modificações no ambiente, tanto de origens naturais quanto antropogênicas, as quais afetam diretamente a estrutura das populações de aves. Tais variações podem ser detectadas por meio de alterações na abundância e na riqueza de espécies de aves (Pozza e Pires, 2003;Dario, 2008). A avifauna florestal responde a essas alterações de forma que sua abundância e composição variam conforme o tamanho dos fragmentos e a estrutura fitofisionômica, com locais mais preservados permitindo a ocorrência de aves mais especializadas, como aves que dependem de sub-bosque, e áreas com fragmentos menores permitindo a ocorrência de aves de ambientes abertos (Brummelhaus et al, 2012).…”
Section: Introductionunclassified